Thermoregulated gas transport through electrospun nanofiber membranes. (17th February 2015) - Han, Sangil; Rutledge, Gregory C.
Abstract: Thermoregulation of gas transport using electrospun fiber membranes is demonstrated experimentally for the first time. The fiber membranes comprise three layers: a middle layer of electrospun polystyrene sandwiched between two outer layers of electrospun cellulose acetate mat as supports, bonded together by hot pressing. The electrospun polystyrene layer serves as a phase change material that blocks transport of gases though the membrane when the fibers de-vitrify. The membrane exhibited a reduction in oxygen flux at temperatures in excess of 140 °C. Using a blend of polysulfone and polystyrene resulted in an upward shift of the transition temperature to 250 °C. Modeling of transport was performed to estimate the impact of the morphological properties of the membranes such as tortuosity, fiber diameter, and porosity. Highlights: The developed membranes showed the flux decrease with temperature increase. Three-layered electrospun membranes were developed by electrospinning and hot pressing techniques. Transition temperature of flux decrease was controlled by blending of polystyrene and polysulfone. Modeling of transport was performed to estimate the impact of the morphological properties of the membranes.